High-normal free thyroxine levels are associated with low trabecular bone scores in euthyroid postmenopausal women. Issue 2 (February 2016) - Hwangbo, Y.; Kim, J.; Kim, S.; Park, Y.; Park, D.; Kim, S.; Shin, C.; Cho, N.
Abstract Summary Trabecular bone scores (TBS) have recently been developed as a diagnostic tool to assess bone texture. We studied thyroid status and TBS in a population-based cohort and demonstrated that high-normal thyroxine levels are associated with low TBS in healthy euthyroid postmenopausal women. Introduction Increased thyroid hormone levels affect bone mineral density (BMD) and, if untreated, increase the risk of fracture. However, the relationship between thyroid function and bone microarchitecture has not yet been established. Trabecular bone scores (TBS) are gray-level textural measurements of dual energy X-ray absorptiometry (DXA) images. The TBS has been proposed as an indirect index of bone microarchitecture. The goal of this study was to characterize the relationship between thyroid function and TBS in euthyroid men and postmenopausal euthyroid women. Methods A total of 1376 euthyroid subjects (648 postmenopausal women and 728 men) were recruited from a community-based cohort in Korea. Free thyroxine (fT4) levels, thyroid stimulating hormone (TSH) levels, BMD, and TBS were measured and compared. Results There was no significant relationship between either fT4 or TSH levels and BMD in men and women. Multiple linear regression analysis showed that high-normal fT4 levels were negatively correlated with TBS (β = −0.111;P = 0.002, after adjusting for both age and body mass index [BMI]) in postmenopausal women. In men, however, there was no significant correlation between fT4 levels and TBS. TSH levels were not significantly associated with TBS in either men or women. Conclusion Higher fT4 levels within the normal reference range are associated with deterioration of trabecular microarchitecture in healthy euthyroid postmenopausal women.